Diversification and Design of Novel Aniline‐Pyrimidines via Sonogashira/Suzuki Cross Coupling Reactions Catalyzed by Novel CLPN‐Pd. Issue 47 (16th December 2021) - Ullah, Arif; Liu, Jingjiang; Khan, Afaq Ullah; Khan, Qudrat Ullah; Guo, Fuhu; Nazir, Sadia; Quan, Zhengjun; Wang, Xicun; Alosaimi, Abeer M.; Hussein, Mahmoud A.
Abstract: Aniline‐pyrimidines derivatives, especially Mepanipyrim are used as fungicides and obliging to control several diseases, particularly grey mould (Botrytis cinerea) of vegetables and vines. A series of novel Aniline‐pyrimidines derivatives like Mepanipyrim have been synthesized by using novel strategy via Sonogashira/Suzuki cross‐coupling reaction. High competence, novel and recyclable CLPN−Pd (cross‐linked ploy(ionic liquid)s Nano gels) is used as a catalyst in this synthetic method which we recycled three times. Various characterization like XPS, DLS, XPA, X‐rays, HNMR and CNMR have been done for confirmation of CLPN−Pd. For these two combined reactions we used a lower amount of catalyst, has advantages of wide substrate range, compatibility with multiple functional groups, and higher yields. In this novel technique of diversification two hetero aryl chlorides, 4‐chloro‐6‐methyl‐N‐phenylpyrimidin‐2‐amine and ‐chloro‐6‐methyl‐N‐(p‐tolyl) pyrimidin‐2‐amine with hetero phenyl acetylene and hetero aryl boronic acid delivered the subsequent compounds with reasonable to excellent 50 %–93 % yields. All the diversified compounds have been verified by various spectroscopic analysis such as 1 HNMR, 13 CNMR, and HR‐MS spectral study. The analysis and preliminary conclusion provided some reference value for further development of this kind of research and applications in the future. Abstract : Two different reactions Suzuki/Sonogashira have been developed for the diversification of anilin‐pyrimidines derivatives using highly competent, efficient and novel CLPN−Pd catalyst.